Determinants of brand sabotage among railways consumer in Pakistan - Qasim, Saba (2021)
The brands are faced a new form of harmful consumer behavior in recent years. They face consumers who have turned hostile and who are highly determined to cause harm to the brand. Therefore, the purpose of the study is to investigate the relationship between brand experience, brand reputation, brand relationship quality and consumer brand sabotage with the mediation effect of negative emotion. This study assumed that that brand experience, brand reputation, brand relationship quality and negative emotion contribute towards to the adoption of consumer brand sabotage. The research is based on stimulus organism response theory to fill the gap between branding practices and consumer brand sabotage. The consumer data of this study was collected through systematic intercept survey approach at major railways of Pakistan. The data was analyzed by Partial Least Squares Structural Equation Modelling. The result of the study indicates a significant relationship between brand experience towards negative emotion and consumer brand sabotage with the mediation effect of negative emotion. Brand reputation also has a significant relationship between negative emotion and consumer brand sabotage with the mediation effect of negative emotion. Brand relationship quality has insignificant relationship with negative emotion and also consumer brand sabotage with the mediation effect of negative emotion. The research concludes with recommendations, theoretical contribution, practical and managerial contribution and methodological contribution, as well as limitations and suggestions for future research.